The gravity model specification for modeling international trade flows and free trade agreement effects: a 10-year review of empirical studies - Konstantinos Kepaptsoglou; Matthew G. Karlaftis; Dimitrios Tsamboulas (The Open Economics Journal, 2010)
The gravity model has been extensively used in international trade research for the last 40 years because of its considerable empirical robustness and explanatory power. Since their introduction in the 1960's, gravity models have been used for assessing trade policy implications and, particularly recently, for analyzing the effects of Free Trade Agreements on international trade. The objective of this paper is to review the recent empirical literature on gravity models, highlight best practices and provide an overview of Free Trade Agreement effects on international trade as reported by relevant gravity model-based studies over the past decade.
Keywords: 330; gravity model; review; trade flows; free trade agreements; models; econometric methods